Estimating Credit Risk Premia - Lim, Kian Guan (Institutional Knowledge at Singapore Management University, 2003)
This paper investigates the nature of the credit risk premium adjustments in the Jarrow-Lando-Turnbull model of credit risk spreads. The adjustments relate the equivalent martingale measures to the empirical measures of unconditional transition probabilities. We provide a modi ed version of the risk adjustment that allows a linear partition of the credit spread into an unconditional default component, a recovery component, and the risk premium adjustment. The risk adjustments are related to conditional default risk, illiquidity risk, and other factors not related to recovery e ects. The log-transform of these risk adjustments can be speci ed as linear regressions on a set of macroeconomic variables. Some new insights are gained pertaining to these conditional risks such as a typical upward sloping term structure and sensitivity to short-term Treasury rates and increasing forward rates. The conditional risks appear to be insensitive to market returns. Keywords: Credit Spreads, Risk Adjustments, No-arbitrage equilibrium, Conditional Risks JEL Codes: G120 G210 G330 I am grateful to the referees for providing very useful comments that have helped in the revision of this manuscript. I thank Xia Yihong for many helpful comments. I also thank Cheong Foong Soon for excellent computational assistance in this project. Research support from the Wharton-SMU Research Center is acknowledged. yProfessor of Finance, School of Business, Singapore Management University, 469 Bukit Timah Road, Singapore, 259756.